ON ACTIVE SYNCHROPHASING CONTROL OF VIBRATION FOR A FLOATING RAFT VIBRATION ISOLATION SYSTEM - Yang, Tiejun; Liang, Weilong; Huang, Di; Zhu, Minggang; Liu, Zhigang; Shen, Ying; Brennan, Michael J. [UNESP]; Crocker, M. J.; Pawelczyk, M.; Pedrielli, F.; Carletti, E.; Luzzi, S. (Int Inst Acoustics & Vibration, 2015)
A floating raft vibration isolation system installed on a flexible hull-like structure is described in this paper. Four vibration exciters, in which two counter rotating shafts with the same balanced masses are driven by a phase asynchronous motor, are used to simulate rotating machines on the raft. The phases of the electrical supply to the motors are adjusted by synchrophasing control scheme to reduce the vibration transmitted to the host structure to which the machinery raft is attached. Then active vibration isolation control is applied to the floating raft system with synchrhrophasing control. This kind of active synchrophasing control for the floating raft vibration isolation system is investigated experimentally. At last some results are presented and discussed.